Fringe Benefits Provision, Payroll Policy, and Its Influence on Tax Planning at RSU Bungsu Bandung - Sitanggang, Erikson; Aripin, Zaenal (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2025)
Bungsu General Hospital in Bandung City has implemented several tax planning strategies. These strategies include optimizing tax benefits by providing fringe benefits to employees, such as health benefits and health insurance. In addition, the hospital also uses an efficient payroll policy by considering the difference in payroll between Indefinite Term Employment Agreements (PKWTT) and Certain Term Employment Agreements (PKWT). This is expected to help reduce the tax burden and optimize the available tax benefits. The presentation of this analysis uses a descriptive verification method. The purpose of this study is specifically to find out the relationship between fringe benefits, payroll policies and tax planning. This study used a total sampling technique that resulted in 120 respondents. Primary data were obtained through questionnaires. Data analysis used multiple linear regression and hypothesis testing. The results showed that the provision of Fringe benefits and payroll policies of Indefinite-Term Employment Agreements (PKWTT) and Certain-Term Employment Agreements (PKWT) had an influence on tax planning at Bungsu General Hospital, Bandung City, both partially and simultaneously.